Different effects of nonNMDA and NMDA receptor antagonists (NBQX and dizocilpine) on cortical epileptic afterdischarges in rats - Lojková, D; Zivanović, D; Mares, P (Brain research, 2006)
Excitatory amino acids play an important role in generation of epileptic seizures. To study the participation of different types of their receptors in cortical epileptic afterdischarges, a noncompetitive NMDA receptor antagonist dizocilpine and a competitive AMPA receptor antagonist NBQX were used. Adult rats with implanted epidural stimulation and registration electrodes were pretreated either with NBQX (30 or 60 mg/kg i.p.) or with dizocilpine (0.1 or 0.5 mg/kg i.p.) and low-frequency stimulation of sensorimotor cortical area was repeatedly applied with stepwise increased current intensities. Lower dose of NBQX unexpectedly decreased thresholds for elicitation of spike-and-wave afterdischarges (ADs), clonic seizures accompanying this type of ADs and for transition into the second, limbic type of ADs. Lower dose of dizocilpine increased these three thresholds. Higher doses of either drug did not significantly change threshold intensities. Duration of ADs was also influenced by the two antagonists in opposite directions: higher dose of NBQX resulted in prolongation of ADs mainly due to an increased duration of the spike-and-wave part of ADs whereas dizocilpine shortened ADs in a dose-dependent manner affecting both types of ADs. In addition, NBQX did not influence interhemispheric responses meanwhile dizocilpine moderately suppressed these evoked potentials. According to our results, NMDA receptors are important for generation of cortical epileptic afterdischarges meanwhile the role of AMPA receptors is not clear and has to be analyzed.
Keywords: Dose-Response Relationship, Drug; Dose-Response Relationship, Radiation; Rats; vztah mezi dávkou a účinkem léčiva; Electroencephalography; Epilepsy; evokované potenciály; epilepsie; Evoked Potentials; dizocilpinmaleát; chinoxaliny; Rats, Wistar; vztah dávky záření a odpovědi; elektroencefalografie; krysa rodu Rattus; Excitatory Amino Acid Antagonists; Quinoxalines; mozková kůra; zvířata; Dizocilpine Maleate; Cerebral Cortex; elektrická stimulace; potkani Wistar; Electric Stimulation; antagonisté excitačních aminokyselin; Animals